KEANEKARAGAMAN GLOMEROMYCOTA DI KEBUN RAYA BATURADEN DAN SEKITARNYA DI GUNUNG SLAMET - Kartini Kramadibrata (Research Center for Biology-Indonesian Institute of Sciences, 2013)
The occurrence of arbuscular fungi (AF), a member of Glomeromycota associated with plant in Baturaden Botanic Garden and its surrounding area in Slamet mountain in Central Java was studied. Part of the Botanic Garden is Agathis plantation which was planted for more than 50 years. Soil samples were collected from rhizosphere of Agathis, wild plants and shrub. In order to obtain spores of arbuscular fungi, dried soil samples were wet sieved and decanted. Part of soil samples were pot cultured with Pueraria phaseoloides. The result showed there were eleven species of AF identified from Baturaden Botanic Garden i.e. three species of Acaulospora, one species of Claroideoglomus, one species of Funneliformis, one species of Glomus, one species of Gigaspora, three species of Scutellospora and one species of Sclerocystis. In this study there are two new records of AF in Java i.e. Scutellospora biornata, and S. erythropus, and also new distribution area for S.projecturata.